When a Neonate Is Born, So Is a Microbiota - Coscia, Alessandra (Life (Basel), 2021)
In recent years, the role of human microbiota as a short- and long-term health promoter and modulator has been affirmed and progressively strengthened. In the course of one’s life, each subject is colonized by a great number of bacteria, which constitute its specific and individual microbiota. Human bacterial colonization starts during fetal life, in opposition to the previous paradigm of the “sterile womb”. Placenta, amniotic fluid, cord blood and fetal tissues each have their own specific microbiota, influenced by maternal health and habits and having a decisive influence on pregnancy outcome and offspring outcome. The maternal microbiota, especially that colonizing the genital system, starts to influence the outcome of pregnancy already before conception, modulating fertility and the success rate of fertilization, even in the case of assisted reproduction techniques. During the perinatal period, neonatal microbiota seems influenced by delivery mode, drug administration and many other conditions. Special attention must be reserved for early neonatal nutrition, because breastfeeding allows the transmission of a specific and unique lactobiome able to modulate and positively affect the neonatal gut microbiota. Our narrative review aims to investigate the currently identified pre- and peri-natal factors influencing neonatal microbiota, before conception, during pregnancy, pre- and post-delivery, since the early microbiota influences the whole life of each subject.